Insécurité linguistique en contexte minoritaire algérien : enquête sociolinguistique auprès des locuteurs de Tasahlit - Bachir Bessai (Multilinguales)
The study reports the results of a sociolinguistic survey on the variety of Kabylian spoken in the regions of Kabylia Maritime or what is commonly called "The Sahel". Then we aim to analyze the phenomenon of linguistic insecurity through the study of linguistic representations, its various manifestations among tasahlit speakers.